High Performance Payload Conversion Method. (28th August 2013) - Li, Frank; Tang, Alan; Urie, Alistair; Valenzuela, Reinaldo
Abstract Virtualization technology is becoming more and more popular, and when applicable, telecom equipment is being migrated to virtualized platforms. While virtualization technology provides many benefits, it also presents significant challenges. For example, the special hardware used for audio payload conversion can no longer be used. In legacy telecom equipment, the user plane, which processes voice over Internet Protocol (IP), was designed to use special hardware such as field programmable gate array/complex programmable logic devices (FPGA/CPLD) for optimum performance. However, in virtualized platforms the only choice is a general‐purpose processor and therefore software‐based payload conversion algorithms have to be used accordingly. This introduces a major performance issue in that a software‐only solution is needed to reach the performance levels already possible with legacy equipment, and the prospect of reaching this goal using a software‐based algorithm is a very challenging task. This letter describes our work to use a virtualized machine to replace the CPLD board used to convert the VoIP payload packets from the Real Time Transport Protocol (RTP) to the Transcoder and Rate Adaptation Unit over IP (TRAUP) protocol and vice versa. We also describe a conversion method that we developed to improve performance. © 2013 Alcatel‐Lucent.